THE INFLUENCE OF COMMUNICATION, ORGANIZATIONAL CULTURE AND THE RELATIONSHIP OF MASS MEDIA TO PERFORMANCE DEFENSE UNIVERSITY OFFICER - Sri Murtiana; Sundring Pantja Djati; Ari Saptono (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The goal to be achieved by an organization is to improve existing performance for the better. Performance is influenced by communication, communication, organizational culture, and mass media relations in its implementation. The problems discussed in this study are the influence of Communication, Organizational Culture, and Mass Media Relations on the Performance of Defense University Employees. The methodology used in research tries to make a systematic, factual, and accurate picture of the facts and properties of a particular object. The sample used was 302 people. In conclusion, communication, organizational culture, and intense media relations will create good employee performance. At the same time, the implications of communication, corporate culture, and good mass media relations will make reliable employee performance. Recommendations for improving communication, organizational culture, and mass media relations so that employee performance will be more optimal.